RETRACTED: Pengasuhan Anak Usia Dini pada Keluarga Dayak Desa yang tinggal di Rumah Betang Ensaid Panjang - Fransiska Fransiska; Suparno Suparno (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
RETRACTION TO:Fransiska, F., Suparno, S. (2019). Pengasuhan Anak Usia Dini Pada Keluarga Dayak Desa Di Rumah Betang Ensaid Panjang. Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini, 10(02), 83-92.This article has been retracted by Publisher based on the following reason:The Editor of Cakrawala Dini: Jurnal Pendidikan Anak Usia Dini found the double publication in the article publishing due to article's content similarity published in http://www.e-journal.hamzanwadi.ac.id/index.php/jga/article/view/1655/0Fransiska, F., Suparno, S. (2019). Pengasuhan Anak Usia Dini Pada Keluarga Dayak Desa Di Rumah Betang Ensaid Panjang. Jurnal Golden Age, 3(02), 95-106. One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process